1.6k views
2 votes
Combine the like terms to get an equivalent expression: 8r+7−6r−5

User Hukam
by
5.0k points

2 Answers

4 votes

Answer:

2r + 2

Explanation:

8r+7−6r−5

Terms with r are like terms and can be combined together.

Terms with no variable are like terms and can be combined together.

Terms with r and terms with no r are not like terms and cannot be combined together.

8r + 7 - 6r - 5 =

= 8r - 6r + 7 - 5

= 2r + 2

User Julien
by
4.8k points
7 votes

Answer:

the correct answer would be 2r+2

Explanation:

8r-6r=2r

7-5=2

User Kahlua
by
5.1k points